Analisis Risiko Gangguan Otot Rangka Pada Pengrajin Tenun Sulam Tapis - Rahmawati, Ernita; Modjo, Robiana (FORIKES, 2024)
Weaving “Tapis” embroidered cloth, which is a traditional industry in Lampung, Indonesia, has become a risky job for craftsmen operating in the informal sector. Complaints related to musculoskeletal disorders have become a significant problem among weaving industry workers, especially tapis embroidery craftsmen. This study aimed to analyze the risk of musculoskeletal disorders in tapis embroidery weaving craftsmen using a systematic review approach, following the Preferred Reporting Items for Systematic Review and Meta Analysis (PRISMA) guidelines. The study was conducted in August 2023 by searching for articles in leading sources such as Google Scholar, ProQuest, ScienceDirect, and Taylor & Francis. Article searches were carried out using the PICO (Participants, Interventions, Comparisons, Outcomes) framework until March 2023 with relevant inclusion criteria. This review involveed eight articles relevant to the risk of musculoskeletal disorders in weaving craftsmen. It was concluded that weaving work significantly involves unergonomic body postures and repetitive hand movements, increasing the risk of musculoskeletal disorders in weaving workers. Individual and occupational factors, such as age, long working years, high body mass index, lack of physical activity, short sleep duration, not using a sitting pillow, and a history of diseases such as dyslipidemia, can be potential triggers for musculoskeletal disorders.Keywords: risk analysis; musculoskeletal disorders; weaving craftsmen; Tapis embroidery ABSTRAK Penenunan kain sulam “Tapis”, yang merupakan industri tradisional di Lampung, Indonesia, telah menjadi pekerjaan yang penuh risiko bagi pengrajin yang beroperasi disektor informal. Keluhan terkait musculoskletal disorders telah menjadi masalah yang signifikan dikalangan pekerja industri tenun terutama pengrajin kain sulam tapis. Studi ini bertujuan untuk menganalisis risiko musculoskletal disorders pada pengrajin tenun sulam tapis dengan menggunakan pendekatan systematic review, mengikuti pedoman Preferred Reporting Items for Systematic Reviev and Meta Analysis (PRISMA). Studi dilakukan pada bulan Agustus 2023 dengan melakukan pencarian artikel di sumber-sumber terkemuka seperti Google Scholar, ProQuest, ScienceDirect, dan Taylor & Francis. Pencarian artikel dilakukan dengan mengunakan kerangka PICO (Participants, Interventions, Comparisons, Outcomes) hingga Maret 2023 dengan kriteria inklusi yang relevan. Tinjauan ini melibatkan delapan artikel yang relevan dengan risiko musculoskletal disorders pada pengrajin tenun. Disimpulkan bahwa pekerjaan penenunan secara signifikan melibatkan postur tubuh yang tidak ergonomis dan gerakan tangan berulang, meningkatkan risiko musculoskletal disorders pada pekerja penenun. Faktor-faktor individu dan pekerjaan, seperti usia, masa kerja yang panjang, indeks massa tubuh tinggi, kurangnya aktivitas fisik, durasi tidur pendek, tidak menggunakan bantal duduk, dan adanya riwayat penyakit seperti dyslipidemia, dapat menjadi pemicu potensial terjadinya gangguan otot rangka.Kata kunci: analisis risiko; musculoskletal disorders; pengrajin tenun; sulam Tapis